2014
DOI: 10.1007/s00418-014-1220-3
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase and actin regulator 4 is associated with intermediate filaments in adult neural stem cells and their progenitor astrocytes

Abstract: Phosphatase and actin regulator 4 (Phactr4) is a newly discovered protein that inhibits protein phosphatase 1 and shows actin-binding activity. We previously found that Phactr4 is expressed in the neurogenic niche in adult mice, although its precise subcellular localization and possible function in neural stem cells (NSCs) is not yet understood. Here, we show that Phactr4 formed punctiform clusters in the cytosol of subventricular zone-derived adult NSCs and their progeny in vitro. These Phactr4 signals were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, previous studies have found only limited evidence for parallel patterns of spatially-varying selection in Atlantic eels ( Ulrik et al 2014 ). Among the five candidate genes shared between species, three ( pactr4b , SNX14 , and SHANK3 ) are implicated in brain development ( Cho et al 2014 ; Ha et al 2015 ; Kozol et al 2015 ), perhaps reflecting similar selective constraints on this biological pathway in the two species.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have found only limited evidence for parallel patterns of spatially-varying selection in Atlantic eels ( Ulrik et al 2014 ). Among the five candidate genes shared between species, three ( pactr4b , SNX14 , and SHANK3 ) are implicated in brain development ( Cho et al 2014 ; Ha et al 2015 ; Kozol et al 2015 ), perhaps reflecting similar selective constraints on this biological pathway in the two species.…”
Section: Discussionmentioning
confidence: 99%
“…Tissues were isolated and incubated with Accutase (Innovative Cell Technologies) for 5 min at 37°C. Dissociated cells were seeded on an ultralow attachment surface of a six-well dish and maintained as neurospheres in N2 media containing 1% serum-free N2, 2% B27 supplement, and 1% penicillin-streptomycin (Gibco BRL) in DMEM/F12 medium (Welgene) as previously described [20]. Neurospheres were grown for 7 days in culture media containing basic fibroblast growth factor (bFGF, 20 ng/ mL; R&D) and epidermal growth factor (EGF, 20 ng/mL; Invitrogen).…”
Section: Nsc Culturementioning
confidence: 99%
“…Adult mouse were sacrificed and the brain was isolated. After making 1-mm brain slices, the Subventricular zone (SVZ) tissues were isolated and incubated with digestion buffer including 0.8% papain (Worthington, Lakewood, NJ, USA) and 0.08% dispase II (Roche Applied Science) in HBSS for 45 min at 37 °C) 43 . Dissociated cells were seeded and maintained as neurospheres in DMEM/F12 media containing 1% N2, 2% B27, and penicillin-streptomycin.…”
Section: Methodsmentioning
confidence: 99%